KAJIAN IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY PERBANKAN SYARIAH DITINJAU DARI SHARIAH ENTERPRISE THEORY PADA PT. BANK PEMBIAYAAN RAKYAT SYARIAH BHAKTI SUMEKAR CABANG PAMEKASAN - - Samsiyah; Yudhanta Sambharakhresna; Nurul Kompyurini (Universitas Trunojoyo Madura, 2013)
The objective of this study is to analyze the implementation of corporate social responsibility (CSR) of syariah banking based on the shariah enterprise theory. This study explore how BPRS Bhakti Sumekar apply its company social responsibilities. It uses observation method, interview method, and documentation method towards parties responsible to implement CSR and uses analyses based on disclosure items of social responsibilities of shariah enterprise theory. The results shows that CSR implementation of PT. BPRS Bhakti Sumekar is still very limited, performed voluntarily, and still far in the way to correspond to the shariah enterprise theory.